Sphingosine-1-phosphate reduces ischaemia–reperfusion injury by phosphorylating the gap junction protein Connexin43. (13th January 2016) - Morel, Sandrine; Christoffersen, Christina; Axelsen, Lene N.; Montecucco, Fabrizio; Rochemont, Viviane; Frias, Miguel A.; Mach, Francois; James, Richard W.; Naus, Christian C.; Chanson, Marc; Lampe, Paul D.; Nielsen, Morten S.; et al.
Abstract: Aim: Increasing evidence points to lipoprotein composition rather than reverse cholesterol transport in the cardioprotective properties of high-density lipoproteins (HDLs). HDL binding to receptors at the surface of cardiomyocytes activates signalling pathways promoting survival, but downstream targets are largely unknown. Here, we investigate the pathways by which the sphingosine-1-phosphate (S1P) constituent of HDL limits cell death induced by cardiac ischaemia–reperfusion (I/R). Methods and results: Apolipoprotein M (ApoM) transgenic ( Apom-Tg ) mice, in which plasma S1P is increased by 296%, and wild-type (WT) mice were subjected to in vivo I/R. Infarct size, neutrophil infiltration into the infarcted area, and serum Troponin I were less pronounced in Apom-Tg mice. In vitro experiments suggest that this cardioprotection depends on direct effects of S1P on cardiomyocytes, whereas leucocyte recruitment seems only indirectly affected. Importantly, short-term S1P treatment at the onset of reperfusion was sufficient to reduce I/R injury in isolated perfused hearts. Mechanistic in vitro and ex vivo studies revealed that 5 min of S1P treatment induced phosphorylation of the gap junction protein Connexin43 (Cx43) on Serine368 (S368), which was mediated by S1P2 and S1P3, but not by S1P1, receptors in cardiomyocytes. Finally, S1P-induced reduction of infarct size after ex vivo I/R was lost in hearts of mice with a truncated C-terminus of Cx43 ( Cx43 K258/KO ) or in which the S368 is mutated to a non-phosphorylatable alanine ( Cx43 S368A/S368A ). Conclusion: Our study reveals an important molecular pathway by which modulating the apoM/S1P axis has a therapeutic potential in the fight against I/R injury in the heart.